Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1994
DOI: 10.1115/94-gt-174
|View full text |Cite
|
Sign up to set email alerts
|

An Account of Free-Stream-Turbulence Length Scale on Laminar Heat Transfer

Abstract: The effect of length scale in free-stream turbulence is considered for heat transfer in laminar boundary layers. A model is proposed which accounts for an “effective” intensity of turbulence based on a dominant frequency for a laminar boundary layer. Assuming a standard turbulence spectral distribution, a new turbulence parameter which accounts for both turbulence level and length scale is obtained and used to correlate heat transfer data for laminar stagnation flows. The result indicates that the heat transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 17 publications
11
65
2
Order By: Relevance
“…The results are presented below in The correlation was applied to the current data and the results are plotted in From the figure, it is demonstrated that the correlation matches the measured data well for the pressure surface locations, but the suction surface data St' results are much higher than the correlation predicts. This is similar to the result observed for the Dullenkopf and Mayle (1995) correlation.…”
Section: Dullenkopf and Mayle (1995) Effective Turbulence Correlationsupporting
confidence: 82%
See 4 more Smart Citations
“…The results are presented below in The correlation was applied to the current data and the results are plotted in From the figure, it is demonstrated that the correlation matches the measured data well for the pressure surface locations, but the suction surface data St' results are much higher than the correlation predicts. This is similar to the result observed for the Dullenkopf and Mayle (1995) correlation.…”
Section: Dullenkopf and Mayle (1995) Effective Turbulence Correlationsupporting
confidence: 82%
“…In general, results of their tests agreed with those from turbine vane testing in terms of locations of highest heat and mass transfer and early boundary layer transition on the suction surface. Leading edge results agreed well with published correlations from Kestin and Wood (1971) and Dullenkopf and Mayle (1995). Holmberg (1996) studied the effects of small-scale, relatively low intensity turbulence on heat transfer in high-turning turbine blades in transonic flow and measured time-resolved heat flux and velocity.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations